Caracteristicas epidemiológicas, clínicas histopatológicas y quirúrgicas en adolescentes con tumoración de ovario de un hospital nacional - Aquino Cabrera, Noemí Flora (2022)
Objective: To determine the epidemiological, clinical, histopathological and surgical characteristics in patients with ovarian tumors in the child and adolescent population in a hospital in Lima -Peru. Material and method: The study is descriptive, retrospective and cross-sectional. There was a population of 63 patients. The data collection technique was given through previously prepared files where the data from the medical records were recorded. Results: Regarding the epidemiological characteristics, it was obtained that the most frequent age was between 11 to 18 years 85% (n = 63), within the clinical characteristics, the most frequent symptomatology was abdominal pelvic pain 96% (n = 63), also within the histopathological characteristics, the most frequent tumor was the Endometriotic type 47% (n=63) and the most frequently performed surgery was laparotomy 61% (n=63). Conclusions: Ovarian tumors in girls and adolescents have a frequency of 1.5% according to their type of presentation, their form of presentation is still atypical, the vast majority of tumors are benign. Keywords: Cyst; Tumor, Ovary.